Fintech Strategies During COVID-19 and the Pandemic's Impact on Technologies - Alabedi, Ali Jumaah Falih; Ahmed, Dildar Haydar (Research Parks Publishers, 2024)
The COVID-19 pandemic has catalyzed significant transformations in financial technologies (fintech), amidst enduring economic uncertainties and emerging opportunities. This paper systematically reviews literature on fintech disruptions, response strategies, innovations, and implications during the pandemic. Analysis covers pre-crisis fintech trends, the origins of COVID-19 impacts on the industry, digital accelerations in traditional financial services, regulatory and cybersecurity challenges, customer-centric product developments, and potential future collaborations. Findings reveal fintech is poised for growth due to increased digital adoption, financial inclusion demands, and the promise of blockchain technology. However, sustainability hinges on strategic adaptations. Recommendations include public-private partnerships to expand financial access, ethical implementations of emerging technologies, and ongoing research into niche sectors. As fintech's role in global finance grows, these evidence-based insights inform policy and promote responsible innovation, contributing to a comprehensive understanding and identifying key areas for further investigation.